Analisis PIECES untuk Evaluasi Layanan Aplikasi Disney+ Hotstar - Dewi Anggraini P Hapsari; Nurul Adhayanti; Romdhoni Susiloatmaja (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2023)
Disney+ Hotstar is a popular streaming service provider platform that offers a variety of entertainment content to users in various countries. This study aimed to analyze Disney+ Hotstar user satisfaction using the PIECES (Performance, Information, Economics, Control, Efficiency, and Services) method for evaluating the services provided. This method is used to identify the strengths and weaknesses of aspects that affect user satisfaction on this platform. The results of the identification are then used as a reference in the evaluation as an effort to improve service and customer satisfaction. This study uses a quantitative approach. Data collection uses a questionnaire outlined in the Google form to determine user ratings of PIECES aspects. Respondents were 121 Disney+ Hotstar users in the Jakarta area who were randomly selected. Data analysis used descriptive analysis techniques. The study results show that users are very satisfied with the application's performance, the information presented, the efficiency, and the services provided. The challenges are found in the economic aspects and user control, which are satisfactory but still need to be improved to satisfy the user more so that the user is very satisfied with all aspects of PIECES. The recommendations are improvements to the method of transaction and payment methods, more competitive prices, greater guarantees of transaction security, and customer data security. This recommendation aims to increase Disney+ Hotstar user satisfaction and strengthen the platform's position in the increasingly competitive streaming service market